Supervision of Fishery Resources through Integrated Technology - Ramlan, Ramlan; Riza, Faisal (Journal of Progressive Law and Legal Studies, 2024)
Fisheries crimes damage ecosystems and fisheries resources in waters or sea areas. Although various efforts have been made to stop criminal acts in the fisheries sector, fisheries supervision is still carried out. Therefore, policies and implementation systems for monitoring criminal acts in the fisheries sector must be considered because the public, apart from authorized supervisory officers, can supervise fisheries. This research focuses on determining policies and implementation of supervision that uses integrated technology. The normative legal research methods used are the statutory and concept approaches. Researchers also collect data and conduct studies through qualitative analysis. Law Number 45 of 2009, concerning Amendments to Law Number 31 of 2004 concerning Fisheries, is the basis for supervision. Another law included in supervision is Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning the Management of Coastal Areas and Small Islands. According to this research analysis, integrated technology for fisheries monitoring is new and needs to be taken seriously by various legislative policies.